Klasifikasi Desa Wisata di Provinsi Jawa Tengah Menggunakan Algoritma C4.5 - Leniawati, Nimas; Wijayanto, Sena (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2024)
Central Java is part of a province on the island of Java that develops the tourism industry. Based on Central Java provincial regulation No. 2 of 2019, regarding the empowerment of tourism villages in Central Java Province, it is stated that tourism villages play an important role in advancing public welfare, equitable distribution of trade and employment, optimization of economic potential and regional characteristics, as well as promoting and protecting cultural, religious, and national values and natural preservation. This relates to the importance of identifying tourist villages that can be developed as tourist destinations. For this reason, classification in data mining can be done using the C4.5 algorithm. The C4.5 algorithm can be used in obtaining a decision tree that is easy to understand in classifying tourist villages. This research aims to classify tourist villages by implementing the decision tree classifier C4.5 algorithm. The research data was obtained from the Central Java Province data portal dataset in 2019 and the problem solving in this study raised the Knowledge Discovery Database process. The results of this study are in the form of testing the C4.5 algorithm using confusion matrix and obtaining accuracy of 86%, recall of 88% and precision of 86%.